The transmissible spongiform encephalopathies: emerging and declining epidemics. (25th October 2006) - Manson, J.C.; Cancellotti, E.; Hart, P.; Bishop, M.T.; Barron, R.M.
Abstract : TSEs (transmissible spongiform encephalopathies) are neurodegenerative diseases of various mammalian species, the best known of which include BSE (bovine spongiform encephalopathies) in cattle, CJD (Creutzfeldt–Jakob disease) in humans, scrapie in sheep and CWD (chronic wasting disease) in deer. This review examines the emergence of various TSE strains and their transmission, and discusses disease surveillance and control.